2005
DOI: 10.1149/1.1997167
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Study of the Electroless Deposition of Co(W, B) Alloys

Abstract: This paper presents the results of a study of the electroless deposition process and the film properties of cobalt-tungsten-boron ͓Co͑W, B͔͒ thin layers on thin copper films. Two solutions based on cobalt citric complexes and dimethylaminoborane reducing agent were developed. Tungsten was introduced into the solutions by using either sodium tungstate or tungsten acid. The deposited thin-film composition was characterized as a function of the bath formulation by X-ray photoemission spectroscopy. Electroless dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…SEM images (data not shown) of the MWCNTs after electroless silver deposition at pH ¼ 10 indicated that the amount of deposit increased compared to that for deposition at pH ¼ 7.5. Sverdlov et al reported that the anodic reaction of the DMAB reducing agent on the catalytic surface in alkaline solution could be described as follows 33 …”
Section: Resultsmentioning
confidence: 99%
“…SEM images (data not shown) of the MWCNTs after electroless silver deposition at pH ¼ 10 indicated that the amount of deposit increased compared to that for deposition at pH ¼ 7.5. Sverdlov et al reported that the anodic reaction of the DMAB reducing agent on the catalytic surface in alkaline solution could be described as follows 33 …”
Section: Resultsmentioning
confidence: 99%
“…Tel. : +82 31 219 2389; fax: +82 31 219 1612. cap copper interconnections with cobalt-containing films such as Co-P, Co-W-P, Co-W-B and Co-Mo-P [1,[9][10][11][12] and nickelcontaining films such as Ni-P, Ni-W-P and Ni-Re-P [13,14]. Among the above-mentioned metallic capping/barrier layers, it was reported that the Co-W-P films had better performance as an effective capping/barrier layer for copper metallization up to 550 • C [3,16].…”
Section: Introductionmentioning
confidence: 99%
“…Co-W-P thin films can be deposited by both electroless [10][11][12] and electrochemical [17][18][19][20] deposition methods. The electroless plating, however, is widely used to deposit the metallic capping/barrier layers because it is a very simple and inexpensive method, does not require much instrumentations and offers highly selective and conformal deposition [5,12,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-W-P thin films can be fabricated by both electroless [8][9][10][11] and electrochemical deposition methods [12][13][14][15]. Recently, it has been reported that electrodeposition method has some advantages over electroless deposition such as lower processing temperature, better control over the deposition technique and thus, a wide range of compositions [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%